Broad‐Spectrum Catalysts for the Ambient Temperature Anti‐Markovnikov Hydration of Alkynes1. (25th June 2014) - Li, Le; Zeng, Mingshuo; Herzon, Seth B.
Abstract Anti‐Markovnikov alkyne hydration provides a valuable route to aldehydes. Half‐sandwich ruthenium complexes ligated by 5, 5′‐bis(trifluoromethyl)‐2, 2′‐bipyridine are remarkably active for this transformation. In the presence of 2 mol % metal, a wide range of functionalized aliphatic and aromatic alkynes are hydrated in high yield at ambient temperature.